2005
DOI: 10.1002/cncr.21294
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus pneumonia in patients with lymphoma

Abstract: The incidence of CMVp in patients with lymphoma is increasing. CMV detection in BAL specimens was better with culture methods than with cytologic or immunohistochemical methods. High APACHE II score and development of antiviral toxicity were associated with a fatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 27 publications
3
43
1
1
Order By: Relevance
“…The incidence of CMV infection and disease is less clearly defined for patients with haematological malignancies who receive conventional therapy. Investigators at the MD Anderson Cancer Center have reported an overall increase in CMV gastrointestinal disease [57], and CMV pneumonia among patients with lymphoma [58] and acute leukemia [59]. In the absence of effective antiviral prophylaxis, the incidence of CMV infection among patients with haematological malignancy ranges from 5-75%.…”
Section: Other Viral Infectionsmentioning
confidence: 99%
“…The incidence of CMV infection and disease is less clearly defined for patients with haematological malignancies who receive conventional therapy. Investigators at the MD Anderson Cancer Center have reported an overall increase in CMV gastrointestinal disease [57], and CMV pneumonia among patients with lymphoma [58] and acute leukemia [59]. In the absence of effective antiviral prophylaxis, the incidence of CMV infection among patients with haematological malignancy ranges from 5-75%.…”
Section: Other Viral Infectionsmentioning
confidence: 99%
“…Investigators at the MD Anderson Cancer Center have reported a series of retrospective studies on the incidence of CMV disease among patients receiving conventional therapy. [20][21][22] These investigators reported an overall increase in CMV gastrointestinal disease during the past two decades, and CMV pneumonia was also increased among patients with lymphoma and acute leukemia. CMV-attributable mortality for these patients ranged from 30% to 57%.…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…In this population, CMV antigenemia has been reported only in small series or case studies (7)(8)(9). Even among SCT and organ transplant recipients, largescale epidemiologic studies performed to determine the effects of underlying diseases (and associated treatment), sex, age, and ethnicity on antigenemia are scanty.…”
mentioning
confidence: 99%